MEMLÛK-KIPÇAK SAHASINDA YAZILMIŞ ALTI DİLLİ KRAL’IN SÖZLÜĞÜNDE İKİLİ-ÇOKLU KELİME VE ŞEKİLLER - Can ÖZGÜR (Fırat University, 2019)
Abstract The book called as The King's Dictionary with 6 languages (Arabic, Persian, Turkish, Greek, Armenian and Mongolian) having been prepared by Al- Melik al Afdal-Abbas b. Ali from Rasul's dynasty in Yemen in 14th Century is a dictionary. Binary-multiple words and forms which are placed in Turkish part of this work of art are analyzed. The examples complicated and forms: e- : i- ; -e- : -i-, -a- : -u- ; -a- : -ı- ; -e- : -i- : -ı- : -u- : -i- : -ü-, b- : m-, p- : m- ; p- : b-, -d-, -?- : -y-, ñ : n, t- : d- ; -t- : -d- ; -t : -d,? : t, -?- : -?-, y- : Ø ; -y : Ø, -g, -g : Ø, b- : Ø, t- : Ø, bol- : ol- and other examples. The King's Dictionary is a remarkable work because of reflecting the features of mixed dialects in the14th century in Mamluk's geography. Key Words: The King's Dictionary, binary-multiple, complicated words and forms.